The Epidemiology of Bloodstream Infections and Antimicrobial Susceptibility Patterns: A Nine-Year Retrospective Study at St. Dominic Hospital, Akwatia, Ghana - John Gameli Deku; Mavis Puopelle Dakorah; Sylvester Yao Lokpo; Verner N. Orish; Francis Abeku Ussher; Godsway Edem Kpene; Vida Angmorkie Eshun; Eunice Agyei; Waldermer Attivor; James Osei-Yeboah (Journal of Tropical Medicine)
Background. Bloodstream infections are among the top causes of morbidity and mortality in people of all ages, especially in immunocompromised patients in sub-Saharan Africa. This study aimed at describing the epidemiology of bloodstream infections and antimicrobial susceptibility pattern over a nine-year period at St. Dominic Hospital, Akwatia, in the Eastern Region of Ghana. Method. This study retrospectively analysed data from 4,489 patients who were referred to the Laboratory Department for blood culture and sensitivity testing from January 2009 to December 2017. Sociodemographic data included age, gender, and patients’ department. Blood culture results were retrieved from archival records in the laboratory. The authorities of St. Dominic Hospital granted approval for the study. Results. The incidence of bloodstream infection over the 9 years was 51.4 positive cultures per 100,000 hospital attendance. Staphylococcus aureus was the leading causative agent of bacteraemia for the first two scalar years (2009–2011 (38.9%) and 2012–2014 (42.2%)) while coagulase-negative staphylococcus (CoNS) (50.5%) was predominant for the last scalar year (2015–2017), followed by Staphylococcus aureus (169/587 (28.8%)). The highest incidence of bloodstream infections was recorded in the wet seasons (months of May (8.9 per 10,000 persons) and October (10.1 per 10,000 persons)). The bacterial isolates demonstrated high resistance to tetracyclines (390/531 (73.4%)), penicillins (1282/1669 (76.8%)), and sulphonamides (450/499 (90.2%)). Conclusion. Bloodstream infection and antimicrobial resistance are high in patients seeking healthcare in Akwatia. This therefore calls for concerted efforts aimed at reducing the incidence in the study area.